2016
DOI: 10.2217/imt-2016-0014
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Modifiers in Immunotherapy: a Focus on Checkpoint Inhibitors

Abstract: Immune surveillance should be directed to suppress tumor development and progression, involving a balance of coinhibitory and costimulatory signals that amplify immune response without overwhelming the host. Immunotherapy confers durable clinical benefit in ‘immunogenic tumors’, whereas in other tumors the responses are modest. Thus, immune checkpoint inhibitors may need to be combined with strategies to boost immune response or increase the tumor immune profile. Epigenetic aberrations contribute significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 127 publications
(129 reference statements)
0
43
0
1
Order By: Relevance
“…This study also reported that mice treated with PD-L1 checkpoint blockade or DZNep (an inhibitor of all SAM-dependent enzymes) plus DAC exerted a decreased tumor size, increased CD8+ T lymphocytes and Th1-type chemokine expression [27]. Therefore, the inhibition of DNA hypermethylation synergistically increases the therapeutic efficacy of anti-PD-L1 therapy [117]. To evaluate the correlation of immune checkpoints (PD-L1, PD-L2, PD-1 and CTLA-4) with DNMTi in patients with myeloid malignancies, a study evaluated the effect of the treatment of leukemia cells with DAC and revealed that DAC leads to a dosedependent upregulation of these 4 genes [118].…”
Section: Dnmti Boosts Tumor Immune Checkpoint Markermentioning
confidence: 67%
“…This study also reported that mice treated with PD-L1 checkpoint blockade or DZNep (an inhibitor of all SAM-dependent enzymes) plus DAC exerted a decreased tumor size, increased CD8+ T lymphocytes and Th1-type chemokine expression [27]. Therefore, the inhibition of DNA hypermethylation synergistically increases the therapeutic efficacy of anti-PD-L1 therapy [117]. To evaluate the correlation of immune checkpoints (PD-L1, PD-L2, PD-1 and CTLA-4) with DNMTi in patients with myeloid malignancies, a study evaluated the effect of the treatment of leukemia cells with DAC and revealed that DAC leads to a dosedependent upregulation of these 4 genes [118].…”
Section: Dnmti Boosts Tumor Immune Checkpoint Markermentioning
confidence: 67%
“…In addition to the initiation of ICD, the ability of conventional chemotherapies to upregulate MHC classes I and II enables malignant cells to be better recognized and destroyed by the immune system [43,44]. Tumor-Associated Antigens (TAAs) are presented on MHC class I to CD8 + cytolytic T cells, which can then directly eliminate cancer [45].…”
Section: Impact Of Chemotherapy On Anti-tumor Immunity and Cancer mentioning
confidence: 99%
“…Not surprisingly, HDACi can modify the expression of inhibitory molecules (Figure 3) [44]. For example, class I HDACi were demonstrated to upregulate PD-L1/L2 surface protein and RNA transcription in melanoma patients, in melanoma cell lines and in a syngeneic mouse model of melanoma, through acetylation of the PD-L1 and PD-L2 promotor [164].…”
Section: Impact Of Epigenetic Modifiers On Anti-tumor Immunity Camentioning
confidence: 99%
See 1 more Smart Citation
“…Predominant responses to HDACi generally include inhibition of proliferation and induction of cell death, which is linked to efficacy in experimental models, and tumor cell "intrinsic" responses may include modulating tumor immunogenicity (12), priming the immune response by increasing expression of tumorassociated antigens and immune-regulated genes, as well as modulating chemokines and cytokines involved in immune system activation (13,14). It has also become clear that effects of HDACis are highly dependent upon context and not easily anticipated.…”
mentioning
confidence: 99%